2015
DOI: 10.1007/s10600-015-1419-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Several 3,5- and 3-Substituted Thermopsine Derivatives

Abstract: In continuation of research on functionalization of the 2-pyridone core of quinolizidine alkaloids [1, 2], we synthesized 3,5-dibromo-, 3-bromo-, 3-nitro-, 5-nitro-, and 3-amino-derivatives of the quinolizidine alkaloid thermopsine (1).Thermopsine (1) was obtained in S. Yu. Yunusov Institute of the Chemistry of Plant Substances (Tashkent). Its physicochemical constants agreed with those in the literature [3].Bromination of 1 according to the literature [1] produced 3,5-dibromo-derivative 2 in 73% yield. Compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The NMR spectroscopic data of 11 showed signals for five methylenes, eight methines, and three quaternary carbons. The aforementioned data suggested that 11 was a homolog of thermopsine ( 25 ) . The downfield shifts of C-12 (δ C 54.9, Δδ C + 25.1) and C-13 (δ C 51.6, Δδ C + 27.2), combined with HRESIMS, revealed the existence of a 12,13-epoxide unit in 11 , which can be confirmed by key 1 H- 1 H COSY signals of H 2 -10/H-9/H-11/H-12/H 2 –13/H-14/H-15 (Figure ).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The NMR spectroscopic data of 11 showed signals for five methylenes, eight methines, and three quaternary carbons. The aforementioned data suggested that 11 was a homolog of thermopsine ( 25 ) . The downfield shifts of C-12 (δ C 54.9, Δδ C + 25.1) and C-13 (δ C 51.6, Δδ C + 27.2), combined with HRESIMS, revealed the existence of a 12,13-epoxide unit in 11 , which can be confirmed by key 1 H- 1 H COSY signals of H 2 -10/H-9/H-11/H-12/H 2 –13/H-14/H-15 (Figure ).…”
Section: Resultsmentioning
confidence: 83%
“…The aforementioned data suggested that 11 was a homolog of thermopsine (25). 20 The downfield shifts of C-12 (δ C 54.9, 4). Consequently, the absolute configuration of 7R, 9R, 11R, 12R, 13S for 11 was established by ECD calculations (Figure S7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations